Serum amyloid A – an acute-phase protein involved in systemic sclerosis pathogenesis? - Lis-Święty, Anna; Widuchowska, Małgorzata; Wcisło-Dziadecka, Dominika; Brzezińska-Wcisło, Ligia; J. Kucharz, Eugeniusz (Dermatology Review/Przegląd Dermatologiczny, 2012)
Serum amyloid A (SAA) is a protein contributing to deposition of amyloid in tissues. Secondary amyloidosis develops as a result of a long-standing inflammatory reaction caused by infection or inflammatory disorders in a number of rheumatic diseases such as rheumatoid arthritis, juvenile rheumatoid arthritis and ankylosing spondylitis. Amyloidosis is rarely a complication of systemic sclerosis (SSc), a disease with a relatively low systemic inflammatory compound. Serum amyloid A is also an acute phase protein, which plays a role in the pathogenesis of autoimmune diseases, atherosclerosis and tumours. In this article particular attention is paid to the potential role of SAA in pathological processes in SSc.